Phosphorylated hsp90 alfa as predictive and prognostic biomarker in tumors from patients treated with platinum analogs - Cuello Carrión, Fernando Darío (2019)
The heat shock protein HSP90α is a ubiquitous molecular chaperone specially required for cancer cells as it chaperones proteins involved in oncogenesis, making it an attractive target for anticancer therapy. Phosphorylated HSP90α (P-HSP90α) on the threonine 7 (Thr-7) accumulates at the sites of DNA damage, involving this protein in DNA damage response. In addition, the basal level of P-HSP90α has been proposed as a surrogate biomarker for genetic instability in tumor cells. Platinum analogs (cisplatin, carboplatin) that are widely used for the treatment of many solid tumors damage DNA by forming covalent adducts. Platinum-DNA adducts are bulky lesions that interfere with DNA replication machinery, resulting in the formation of DNA double strand breaks. These lesions can lead to genomic instability and cell death. Unfortunately, the development of resistance to platinum-based agents may limit efficacy of the chemotherapy. Thus, it remains a need for biomarkers of cisplatin-response and prognosis for cancer patients. Our aim was to determine the predictive and prognostic ability of P-HSP90α in primary tumors from cancer patients who received platinum-based chemotherapy (cisplatin/carboplatin). P-HSP90α expression was determined by immunohistochemistry in paraffin-embedded tumor tissues from 51 cancer patients before chemotherapy, with a mean follow-up of 19.2 months. The expression of the protein was evaluated according to a staining intensity score and proportion of positive tumor cells. Clinical response was assessed after the third cycle of chemotherapy. Disease-free (DFS) and overall survival (OS) were periodically determined. Patients with complete clinical response or partial response to chemotherapy showed nuclear expression of P-HSP90α in contrast with tumors from patients with stable disease or progressive disease (P<0.01). In addition, patients with high cytoplasmic proportion of P-HSP90α had a significantly worse OS (P<0.05). No statistically significant relationship was found between P-HSP90α expression and DFS. Our preliminary results provide evidence that P-HSP90α could be a potentially valuable biomarker in predicting response to platinum-based chemotherapy and, may also be useful for defining the prognosis of the disease.